1981
DOI: 10.1159/000198643
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Radiolucent Gallstones with CDCA or UDCA

Abstract: Patients with radiolucent gallstones (diameter < 1.5 cm) and functioning gallbladder were treated for 6–12 months with CDCA (38 patients, 12–15 mg/kg/day) or UDCA (78 patients randomly allocated to receive 5–6 or 10–12 mg/kg/day). Complete dissolutions and partial plus complete dissolutions were respectively 26 and 58% for CDCA, 14 and 58% for UDCA at the lower dose, and 29 and 71 % for UDCA at the higher dose. Statistical analysis did not show any significant difference between the three different treatments.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

1982
1982
2003
2003

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…No serious adverse effects of UDCA administration were reported in early controlled clinical trials in patients with gallstone disease, [56][57][58][59] or in long-term, large-scale, placebo-controlled trials in patients with cholestatic liver disease. [11][12][13][14]16 A recent Cochrane review on UDCA in primary biliary cirrhosis revealed that there was no significant increase in total adverse events or severe adverse events in 10 controlled clinical trials.…”
Section: Adverse Effectsmentioning
confidence: 99%
“…No serious adverse effects of UDCA administration were reported in early controlled clinical trials in patients with gallstone disease, [56][57][58][59] or in long-term, large-scale, placebo-controlled trials in patients with cholestatic liver disease. [11][12][13][14]16 A recent Cochrane review on UDCA in primary biliary cirrhosis revealed that there was no significant increase in total adverse events or severe adverse events in 10 controlled clinical trials.…”
Section: Adverse Effectsmentioning
confidence: 99%
“…32 We have also shown that bedtime administration of CDCA is more effective than mealtime administration in improving the gall stone dissolution rate. 33 Previous studies have expressed their results in terms of the percentage of patients who achieve partial or complete gall stone dissolution, or both, within a defined time.22-24 26 28 12 34 The disadvantage ofthese studies is that only those patients who achieved complete dissolution are used for statistical analysis, and therefore there is a requirement for large numbers of patients to be enrolled, or for long periods of treatment follow up. This has prevented the demonstration of clearcut differences between the two bile acids.…”
mentioning
confidence: 99%
“…Urso treatment leads to dissolution of cholesterol gallstones in man (1)(2)(3)(4)(5)(6)(7)(8)(9). Oral administration of Urso increases Urso in bile and decreases the biliary cholesterol (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17).…”
mentioning
confidence: 99%